Work Motivation as Intermediary in Influencing Work Fatigue of Gen-Z Employees - Kadarningsih, Ana; Nusair, Ahmad Ershaid (Fakultas Ekonomi, Universitas Semarang, 2024)
Generation Z or Gen-Z is a generation that was born and grew up in an era of continuously developing technology. Surveys show that more than fifty percent of the generation Z workforce experiences work burnout. This research wants to look again at whether it is true that workers in the Gen-Z age get tired more quickly than previous generations. The aim of this research is also to look at the factors that influence work fatigue for employees belonging to the Gen-Z age group, namely those born between 1995 and 2012. The determining factors for Gen-Z employee fatigue are determined by two factors, namely the work environment and working hours. Apart from that, there is an intermediary factor, namely work motivation, which influences work fatigue. The population of this study were employees of the Central Java Regional Financial Agency with a sample of 111 Gen-Z employees. The analysis method uses convergent tests, reliability tests, hypothesis testing with the SmartPls Version 3 analysis tool. The results of this study found that only the working hours variable determines work motivation and work fatigue in generation Z employees. Meanwhile, work environment variables have no influence on work motivation and work burnout in Gen-Z employees. The limitations of this research are the small number of employees and not separating female and male employees. Future research could use the gender variable as a control variable. Apart from that, the research object can be extended to employees who work in shifts or employees who have flexible working hours such as online drivers or supermarket workers who open shops 24 hours.